EVALUASI DAN NILAI MANFAAT EKONOMI ATAS PROGRAM UPAYA KHUSUS SAPI INDUKAN WAJIB BUNTING (UPSUS SIWAB) PADA TERNAK SAPI PERAH DI KABUPATEN GARUT - Achmad Firman; Lilis Nurlina; Anita Fitriani (Universitas Galuh Ciamis, 2020)
This study aims to evaluate the implementation and economic benefit value of UPSUS SIWAB) in dairy cattle in Garut Regency. The evaluations included body condition score (BCS), service per conception (S/C), and the economic benefit value of the UPSUS SIWAB program on dairy cattle businesses in Garut Regency. Determination of sample location was done purposively with the consideration that the area is adaptive to dairy cattle business. The selected sub-districts are Cikajang, Cilawu and Bayongbong. The results showed that 46.9% of dairy cows were thin and very thin, the S/C value was 1.7, and the estimated value of economic benefits was Rp 172,200,000.